A Novel Rhein Derivative Modulates Bone Formation and Resorption and Ameliorates Estrogen‐Dependent Bone Loss. (5th November 2018) - Jiang, Min; Wang, Tianqi; Yan, Xueming; Liu, Zhuochao; Yan, Yufei; Yang, Kai; Qi, Jin; Zhou, Hanbing; Qian, Niandong; Zhou, Qi; Chen, Bo; Xu, Xing; et al.
ABSTRACT: Osteoporosis, an osteolytic disease that affects millions of people worldwide, features a bone remodeling imbalance between bone resorption by osteoclasts and bone formation by osteoblasts. Identifying dual target‐directed agents that inhibit excessive bone resorption and increase bone formation is considered an efficient strategy for developing new osteoporosis treatments. Rhein, a natural anthraquinone, can be isolated from various Asian herbal medicines. Rhein and its derivatives have been reported to have various beneficial pharmacological effects, especially their bone‐targeting ability and anti‐osteoclastogenesis activity. Moreover, hydrogen sulfide (H2 S) was reported to prevent ovariectomy‐ (OVX‐) induced bone loss by enhancing bone formation, and sulfur replacement therapy has been considered a novel and plausible therapeutic option. Based on this information, we synthesized a rhein‐derived thioamide (RT) and investigated its effects on bone resorption and bone formation in vitro and in vivo. It has been found that the RT‐inhibited receptor activator of the nuclear factor‐κB (NF‐κB) ligand‐ (RANKL‐) induced osteoclastogenesis and bone resorption in a dose‐dependent manner. The expression of osteoclast marker genes was also suppressed by RT treatment. Furthermore, exploration of signal transduction pathways indicated that RT markedly blocked RANKL‐induced osteoclastogenesis by attenuating MAPK pathways. However, RT treatment in an osteoblastic cell line, MC3TE‐E1, indicated that RT led to an increase in the deposition of minerals and the expression of osteoblast marker genes, as demonstrated by Alizarin Red staining and alkaline phosphatase activity. Importantly, an OVX mouse model showed that RT could attenuate the bone loss in estrogen deficiency‐induced osteoporosis in vivo with a smart H2 S‐releasing property and that there was a considerable improvement in the biomechanical properties of bone. Accordingly, our current work highlights the dual regulation of bone remodeling by the rhein‐derived molecule RT. This may be a highly promising approach for a new type of anti‐osteoporosis agent. © 2018 American Society for Bone and Mineral Research.